2018
DOI: 10.1158/0008-5472.can-17-2899
|View full text |Cite
|
Sign up to set email alerts
|

A Soft Microenvironment Protects from Failure of Midbody Abscission and Multinucleation Downstream of the EMT-Promoting Transcription Factor Snail

Abstract: Multinucleation is found in more than one third of tumors and is linked to increased tolerance for mutation, resistance to chemotherapy, and invasive potential. The integrity of the genome depends on proper execution of the cell cycle, which can be altered through mechanotransduction pathways as the tumor microenvironment stiffens during tumorigenesis. Here, we show that signaling downstream of matrix metalloproteinase-3 (MMP3) or TGFβ, known inducers of epithelial-mesenchymal transition (EMT), also promotes m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 57 publications
3
38
0
1
Order By: Relevance
“…These results demonstrated that snail is involved in the EMT process of human renal tubular epithelial cells [30]. The promotion of EMT in renal tubular epithelial cells by snail is regulated by many upstream signaling pathways, and Notch signaling pathway is one of them [9]. It was shown that activation of Notch2 and Notch4 promotes the activation of Snail.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…These results demonstrated that snail is involved in the EMT process of human renal tubular epithelial cells [30]. The promotion of EMT in renal tubular epithelial cells by snail is regulated by many upstream signaling pathways, and Notch signaling pathway is one of them [9]. It was shown that activation of Notch2 and Notch4 promotes the activation of Snail.…”
Section: Discussionmentioning
confidence: 77%
“…The expression of snail is regulated by a variety of signaling pathways, including Notch signaling pathway. Recent studies have shown that induction of EMT by Notch signaling pathway in renal tissue requires activation of snail molecule, and the expression of Snail1 is directly regulated by Notch signaling [9]. Thus, Notch / Snail pathway is an important pathological mechanism of renal interstitial fibrosis in DN and may be a potential therapeutic target for interstitial fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although septins neither present motor activity, nor force generation, due to their interactions with the mechanotransduction machinery, they are supposed to have a role in mechanobiology and in the regulation of mechanotransductional pathways (Calvo et al 2015;Dolat et al 2014a, b;Simi et al 2018). Potentially affecting the conformation of stretch-sensitive ion channels, they might be able to modify the stretch-activated cellular responses and downstream mechanotransduction (Pardo-Pastor et al 2018;Coste et al 2010).…”
Section: Cellular Function Of Septin Proteinsmentioning
confidence: 99%
“…With the increase concentration of BBR and MET, the number of gastric cancer cells that invaded and metastasized gradually decreased. Matrix metalloproteinase-3 (MMP-3), known as inducers of EMT, is one of the several MMPs that regulate angiogenesis, invasion and metastasis ( Huang et al, 2016 ; Chu et al, 2018 ; Simi et al, 2018 ). It was reported that MMP-3 expression level was negatively correlated with GC development ( Xu et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…With the increased dose of BBR, the number of gastric cancer cells that invaded and metastasized dramatically decreased. MMP-3, known as inducers of EMT, is one of the several MMPs that regulate angiogenesis, invasion and metastasis ( Huang et al, 2016 ; Chu et al, 2018 ; Simi et al, 2018 ).It was reported that MMP-3 expression level was negatively correlated with GC development ( Xu et al, 2016 ). We also found that BBR had stable inhibitory effect on matrix metalloproteinase-3 (MMP-3) protein and mRNA expressions in AGS and SGC7901 cells, which suggested that BBR inhibited the migration and invasion to prevent GC development through downregulating MMP-3 in AGS and SGC7901 GC cells.…”
Section: Discussionmentioning
confidence: 99%